Enhancing Bed Alignment and Reducing Calibration Time in 3D Printers Using Auto Leveling with PI Control - Andreanto Wongsoatmojo; Fransiskus Arjuna Davin Pratama; Ign. R. Haryosuprobo; Alexander Ariantono Nugroho; Bondan Wiratmoko Budi Santoso; Mardiatno (Mechanical Engineering Department - Semarang State Polytechnic, 2026)
Manual bed leveling in fused deposition modeling (FDM) 3D printers is operator-dependent and often produces an uneven nozzle-bed gap, which reduces first-layer adhesion and dimensional repeatability. This study developed a retrofittable auto leveling system based on Proportional-Integral (PI) control for a Cartesian 3D Touch 3D printer at Politeknik ATMI Surakarta. The system combines a 3D Touch probe, three NEMA 17 motorized bed supports, one fixed-jaw reference, DRV8825 drivers, an Arduino Mega 2560, and a Raspberry Pi 4B to measure the bed at nine probing points and physically correct the bed height. Bed deviation was defined as the difference between the maximum and minimum measured height at the bed support reference points. Five Kp-Ki combinations were tested using a 0.05 mm tolerance. The best response was obtained at Kp = 1.0 and Ki = 0.03, completing calibration in 223 s with four iterations and a 0.016 mm deviation. Across five trials, auto leveling reduced the average calibration time from 594.4 s to 255.4 s (57.0%) and reduced the average bed deviation from 0.2228 mm to 0.0232 mm (89.6%) compared with manual leveling. ASTM D638 Type I print validation showed 90% successful squareness. The results demonstrate that PI-controlled physical bed alignment can improve calibration efficiency, repeatability, and first-layer reliability in low-cost FDM printers.